Distance, dams and drift: what structures populations of an endangered, benthic stream fish?. (20th June 2013) - Roberts, James H.; Angermeier, Paul L.; Hallerman, Eric M.
Summary: Spatial population structure plays an important role in species persistence, evolution and conservation. Benthic stream fishes are diverse and frequently imperilled, yet the determinants and spatial scaling of their population structure are understudied. We investigated the range‐wide population genetic structure of Roanoke logperch ( Percina rex ), an endangered, benthic stream fish of the eastern United States. Fish were sampled from 35 sites and analysed at 11 microsatellite DNA loci. Clustering models were used to sort individuals into genetically cohesive groups and thereby estimate the spatial scaling of population structure. We then used Bayesian generalized linear mixed models (BGLMMs) to test alternative hypotheses about the environmental factors most responsible for generating structure, as measured by the differentiation statistic F ST . Clustering models delineated seven discrete populations, whose boundaries coincided with agents of fragmentation, including hydroelectric dams and tailwaters. In the absence of hydrological barriers, gene flow was extensive throughout catchments, whereas there was no evidence for contemporary dispersal between catchments across barriers. In the best‐supported BGLMM, F ST was positively related to the spatial distance and degree of hydrological alteration between sites and negatively related to genetic diversity within sites. Whereas the effect of tailwaters was equivocal, dams strongly influenced differentiation: the effect of a dam on F ST was comparable to that of a between‐site distance of over 1200 km of unimpounded river. Overall, the effect of distance‐mediated dispersal was negligible compared to the combined effects of fragmentation and genetic drift. The contemporary population structure of P. rex comprises a few geographically extensive 'islands' that are fragmented by hydroelectric projects. This information clarifies the importance of a catchment‐scale perspective on conserving the species and suggests that its recovery may require genetic and/or demographic reconnection of presently isolated populations.